Pruning Southern Highbush Blueberry in Florida - Doug Phillips; Jeffrey Williamson (EDIS)
Pruning is an essential part of blueberry production and is used to help establish new plantings; promote postharvest growth of new foliage and fruiting wood; balance vegetative and reproductive growth; reduce disease and certain insect pressure; assist in harvesting efficiency; and promote new cane growth and plant longevity. This new 3-page publication of the UF/IFAS Horticultural Sciences Department is a discussion of pruning practices on southern highbush blueberry in Florida. Written by Douglas A. Phillips and Jeffrey G. Williamson. https://edis.ifas.ufl.edu/hs1359